Mycoparasitic potential of growth promoting Trichoderma strains against phytopathogens - Dwivedi, Meenakshi; Tewari, Anand Kumar (Annals of Agricultural Research, 2018)
Six isolates of Trichoderma asperellum viz. TRS W4, TRP W8, TRS R4, TRS R8, TRP C3 and TRP C4 obtained from rhizosphere and rhizoplane of wheat, rice and chickpea were selected for their growth promoting efficacy in their native crops. These 06 isolates were tested for their biological control potential against plant pathogens viz., Rhizoctonia solani (isolates from rice and chickpea), Sclerotinia sclerotiorum (isolate from chickpea) and Bipolaris sorokiniana (isolate from wheat) under in vitro conditions. Dual culture studyrevealed that all the Trichoderma isolates along with Th-14, commercial Trichoderma harzianum strain used as positive control, completely parasitized, i.e. 100% mycelial parasitiation, the growth of all test plant pathogens.